The Impact of Quizizz Language Learning App in Improving Students' Listening Skills - Pratama*, Fikran Arendi; Rachman, Dzul (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This study investigates the influence of the Quizizz Language Learning App on enhancing students' auditory comprehension abilities in vocational institutions. The study employed a pretest-posttest methodology to assess the listening abilities of students both before and after the integration of Quizizz as an instructional tool. The study involved 25 students from SMK 15 Samarinda, who were evaluated using standardized listening tests conducted on the Quizizz platform. The findings demonstrated a noteworthy enhancement in the listening abilities of the pupils, with an average discrepancy of -32.400 points seen between the scores of the pretest and posttest. The results indicate that Quizizz is a valuable instrument for improving auditory abilities in children attending vocational schools. The study highlights the capacity of gamified educational technology to establish captivating and efficient learning settings, therefore enhancing overall language competency. Additional research is advised to investigate the enduring impacts of Quizizz on different linguistic abilities and its relative efficacy compared to other instructionaltechnologies.